Time course of changes in lipid profile measures in patients with early psoriatic arthritis during adalimumab therapy - E. I. Markelova; D. S. Novikova; T. V. Korotaeva; E. Yu. Loginova (Научно-практическая ревматология)
Patients with psoriatic arthritis (PsA) have a higher risk of cardiovascular disease (CVD) compared with the general population. Inflammation and traditional CVD risk factors (RFs), including dyslipidemia, make a significant contribution to the development of CVD and their complications in patients with PsA.Objective: to assess the time course of changes in lipid profile measures in patients with early PsA (ePsA) during adalimumab (ADA) treatment for 3-months.Subjects and methods. The investigation enrolled 16 patients (11 women, 5 men; median (Me) age, 45.5 years) with early PsA (ePsA) (disease duration, 7.7 months). ADA was administered subcutaneously at doses of 40 mg once every 2 weeks for 3 months. Before and 3 months after the start of ADA therapy, DAS, C-reactive protein levels, and traditional CVD RFs, including lipid profile measures (total cholesterol, TC, low-density lipoprotein cholesterol, LDL-C, triglycerides, TG, high-density lipoprotein cholesterol, HDL-C, and atherogenic coefficient, AC) were estimated. Ten-year risk for fatal CVD was assessed using the SCORE scale.Results and discussion. Lipid profile disorders mainly associated with elevated LDL-C levels were revealed in 11 (69%) patients; according to the SCORE scale, the total 10-year risk for fatal CVD was low and moderate in 10 (62.5%) and 6 (37.5%) patients, respectively. A correlation was found between the baseline DAS and TG (r=0.53; p<0.05) and AC (r=0.57; p<0.05); between HDL levels and DAS (r=-0.68; p<0.05), and between the number of tender (r=-0.63; p<0.05) and swollen joints (r=-0.65; p<0.05).Three months after starting ADA Median level of TC increased from 4.9 [4.5; 5.9] to 5.5 [4.9; 6.3] mmol/L (p=therapy, 15 (94%) patients achieved remission of ePSA; one (6%) patient showed a low disease activity. 0.01) and TG — from 0.8 [0.7; 1.4] to 1.1 [0.9; 1.4] mmol/L (p=0.03). There were no significant changes in the level of LDL-C and HDL-C, and CA, their medians at the beginning and end of therapy were 3.3 [2.8; 4.1] and 3.6 [3.3; 4.1]; 3.0 [1.2; 1.  5] and 1.3 [1.2; 1.6]; 2.6 [2.3; 3.6] and 3.2 [2.4; 3.6] mmol/L, respectively. There was a tendency to increase the frequency of non-target TC values from 44 to 75%, LDL-C from 69 to 81%, TG from 12.5 to 19%, and AC from 37.5 to 62.5% (p>0.05). Conclusion. Lipid profile changes were found in 69% of patients with ePSA and correlated with disease activity. The lower inflammatory activity during ADA therapy was accompanied by elevated TC and TG levels.